1973
DOI: 10.1021/je60059a020
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium-phase properties of n-pentane-carbon dioxide system

Abstract: nesium chloride in the NaCl-MgCI2 system; yet, the excess free energy of mixing is much less.In conclusion, the behavior of the sodium chloridemanganous chloride system is only moderately complicated In that quadratic terms in the Harned expressions are sufficient to give an accurate description of the activity coefficients and that estimates of trace activity coefficients from single salt data are In reasonable agreement with experimental values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(27 citation statements)
references
References 1 publication
2
25
0
Order By: Relevance
“…The pressure transducer connected to a digital multimeter was calibrated at 323.2 K with a precision hydraulic dead-weight tester (model 580C, DH-Budenberg SA, Aubervilliers, France). The uncertainty of the pressures is estimated to be within ± 0.015 MPa using a similar procedure as described in [48], for a pressure range between (0.5 and 20) MPa.…”
Section: Methodsmentioning
confidence: 99%
“…The pressure transducer connected to a digital multimeter was calibrated at 323.2 K with a precision hydraulic dead-weight tester (model 580C, DH-Budenberg SA, Aubervilliers, France). The uncertainty of the pressures is estimated to be within ± 0.015 MPa using a similar procedure as described in [48], for a pressure range between (0.5 and 20) MPa.…”
Section: Methodsmentioning
confidence: 99%
“…1. It consists of four sections: [1] equilibrium cell, [2] sampling device, [3] sample analyzing system, and [4] temperature and pressure measurement device.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been reported that the refractive indices of CO 2 -expanded ethanol and n-pentane at 25 C decrease by $10% when pressurized to 5 MPa. 53,55 Thus, RI values of the continuous and dispersed phases approach each other as the miniemulsion is pressurized, with matching values at P T . At pressures beyond P T , the emulsion once again becomes turbid as the RI of the dispersed phase decreases below that of water.…”
Section: Mechanism Of Miniemulsion Transparencymentioning
confidence: 97%